"The Geordie accent has a bit of a bad reputation": internal and external constraints on stative possession in the Tyneside English of the 21st century: Has possessive got had its day?. (28th May 2015) - Fehringer, Carol; Corrigan, Karen P.
Abstract : The subject of stative possession has generated much interest over the past decade, particularly regarding the origin of the construction have got and its use in different varieties of British and North American English (e.g. Tagliamonte, 2003, 2013; Jankowski 2005; Tagliamonte et al., 2010). In these varieties, have got alternates with have to mark possession in sentences such as those in (1) below. (1) a. We've got a nice lounge there you know, with French doors, and wehave these seats we can take outside and sit (0711b). 1 b. That's the worse type of person. Theyhave nothing and then they've got something and they think they are better than anybody else (0804a).